WORLD FINANCIAL CRISIS AND ITS IMPACT ON THE SERBIAN ECONOMY - Stevanović, Simo; Đorović, Milutin; Milanović, Milan (Economics of Agriculture, 2010)
This paper presents the analysis of occurrence of financial crises in the United States, its spread to the real sector and other countries, as a result of the interconnection of economies in the globalization process. "American dream" that every family has owned the house, which is supported by the favorable state mortgage loans, has led to a rapid jump in prices and higher profits in real estate business. Inclusion of subprimary mortgage market, which approved mortgage loans to low credit customers, increased the number of those who can not settle mortgage obligations in time. On the one hand, by activating the mortgage, in a short time there was found a large number of properties on offer, and on the other hand, due to reduced credit potential of banks due to delays in payments, property prices are falling dramatically. Due to higher mortgage than the market value of property, the banks got into insolvency, which is a mass phenomenon turned into a financial crisis. The financial crisis in the U.S., which grew into a crisis of the real sector, time-delayed half a year, transferred to the Serbian economy. The global financial crisis has just further encouraged and enabled to quickly emerge to the surface of the structural abnormalities, occured well before and during the process of transition in Serbian economy.